READING COMPREHENSION PROBLEMS IN READING SECTION OF TOEFL TEST - Dini Febriani; Elfrida Elfrida; Fernandita Gusweni Jayanti (Universitas Galuh, 2019)
This research aims to find out the reading comprehension problems faced by the eight semester English Education Study Program students of Universitas Bengkulu in Reading Section of TOEFL test. The subject of this research is eight semester students of English Education Study Program in academic year 2018/2019 who have taken TOEFL test in Language Laboratory, FKIP, Universitas Bengkulu. The subject of this research is 70 students of 79 students. This research was used descriptive quantitative as the methodology and the data was collected by using questionnaire as an instrument that distributed via Google-form. The questionnaire consisted of 20 statements which represent 5 aspects of reading comprehension problems by Wutthisingchai (2011). This research uses 4-point Likert Scale to measure students perception of reading problem, ranging from never (1 point), sometimes (2 point), often (3 point), always (4 point). The result shows that the majority of the students have problems in reading comprehension in 5 aspects. The percentage average of each aspect from highest to lowest was the reading comprehension problems related to the Reading Comprehension Process. Second problems is Motivation. Third problems related to Background Knowledge. Fourth related to Lack Reading Strategies. The last problems related to Language Knowledge. From the results, it can be concluded that students of the eight semester at English Education Study Program still have reading comprehension problems.Keywords: Reading comprehension problems, TOEFL Test